2003
DOI: 10.1002/ajim.10227
|View full text |Cite
|
Sign up to set email alerts
|

Beryllium‐stimulated neopterin as a diagnostic adjunct in chronic beryllium disease

Abstract: Neopterin may be a useful diagnostic adjunct in the non-invasive assessment of CBD, differentiating CBD from BeS. Further studies will be required to determine how it performs in workplace screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…We purposely enrolled all study subjects who had a confirmed diagnosis of BeS or CBD, including subjects who had negative or borderline BeLPTs at the time of our analysis, to evaluate the utility of the ELISPOT assay in this population. The sensitivity of the BeLPT (65%) in this study was lower than previously reported 5,6,15 but similar to that recently reported by Maier et al 23 Of the 33 patients with CBD enrolled in this study, 85% showed granulomatous inflammation, and 97% had proliferation of BAL cells in response to beryllium salts. Thus, it is unlikely that the decreased sensitivity of the blood BeLPT is a result of misdiagnosis.…”
Section: Discussionsupporting
confidence: 72%
“…We purposely enrolled all study subjects who had a confirmed diagnosis of BeS or CBD, including subjects who had negative or borderline BeLPTs at the time of our analysis, to evaluate the utility of the ELISPOT assay in this population. The sensitivity of the BeLPT (65%) in this study was lower than previously reported 5,6,15 but similar to that recently reported by Maier et al 23 Of the 33 patients with CBD enrolled in this study, 85% showed granulomatous inflammation, and 97% had proliferation of BAL cells in response to beryllium salts. Thus, it is unlikely that the decreased sensitivity of the blood BeLPT is a result of misdiagnosis.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, authors have found that the combination of elevated neopterin's serum levels with the conventional screening test for CBD, beryllium lymphocyte proliferation test exhibited an optimized positive predictive value suggesting neopterin as a valuable biomarker in discriminating workers with CBD from these that are only sensitized to beryllium rendering lung biopsy unnecessary. These results were substantiated by in-vitro studies of peripheral blood mononuclear cells derived by patients with CBD or beryllium exposed workers [90] and an association between serum levels of neopterin and clinicolaboratory parameters of the disease severity was found. However, further confirmatory tests in large cohorts of patients including serial measurements and correlation of results with clinical and radiological findings are essential to determine reliable cut-off values for the diagnosis of the disease and the assessment of the progression likelihood (Table 5).…”
Section: Serum Biomarkers In Occupational and Environmental Diseasmentioning
confidence: 76%
“…Various studies showed that neopterin can be used as a potential biomarker for immunity-related diseases such as rheumatoid arthritis, malignant processes, sarcoidosis, beriliosis, and interstitial pulmonary diseases [24,[27][28][29][30]. Tzouvelekis et al, 2005 showed the possible use of some serum biomarkers in patients with occupational and environment-related diseases [31].…”
Section: Discussionmentioning
confidence: 99%